PIRANTI EMOTIF DAN TRANSPOSISI MAKNA DALAM WANGSALAN - Danang Wijoyanto (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2023)
Wangsalan is a style of language in Javanese literature that is unique and complicated. Its uniqueness is in the structure and way of production. The structure of the wangsalan consists of the sampiran or opening and the contents. The sampiran or opening of the wangsalan is in the form of a puzzle or a puzzle. The contents of the wangsalan itself are in the form of the message the speaker wants to convey. Between the riddle and the content of wangsalan there is a relationship of meaning but only a relationship of form. The relationship between these forms lies in the answer to the riddle with wangsalan intent. The interpretation of wangsalan is quite complicated because it contains the phenomenon of transposition of meaning. Transposition of meaning in wangsalan occurs in denotative meaning with associative meaning. Transposition of meaning is an attempt to connect differences in lingual forms with the speaker's intention. As a result, separation and discontinuity of form can meet. Therefore, the connecting tool to reconcile these differences is an emotive device. The emotive device acts as a liaison between the puzzle and the intent and content of the wangsalan. There are three emotive tools, namely phonetic, lexical and syntactic. These three tools can be used as principles for producing wangsalan. Based on this discussion, the contribution to learning about wangsalan material is that wangsalan is not only related to sounds but also words. Wangsalan is not classified as a metaphor because the stem or answer and the contents of the wangsalan have no relationship in meaning to the intended characteristics. The relationship is limited to the affinity of form and meaning like a pantun or parikan